Theater as a safe environment to start productive skills development in an EFL classroom - Bertha Ramos Holguín; Jahir Aguirre Morales; Angélica Palacios (Revista Boletín Redipe, 2021)
This article describes a pedagogical proposal based on theater as a safe space to develop productive skills in an EFL classroom. Thirty-six eleventh graders from a public school in Tunja participated in the theater sessions. In each session, we collected data through recordings, interviews, and field notes to understand the impact of the pedagogical intervention. The findings suggested that theater could help créate a safe environment that decreased students’ anxiety levels while exploring the language. As a result, the students’ productive skills started to emerge. We argue the need to change classroom dynamics, organization, and time management in order to create transformative places that foster safe environments in the EFL classroom.